Incidences of Infectious Events in a Renal Transplant Cohort of the German Center of Infectious Diseases (DZIF). (13th May 2022) - Sommerer, Claudia; Schröter, Iris; Gruneberg, Katrin; Schindler, Daniela; Behnisch, Rouven; Morath, Christian; Renders, Lutz; Heemann, Uwe; Schnitzler, Paul; Melk, Anette; Della Penna, Andrea; Nadalin, Silvio; et al.
Abstract: Background: Infectious complications are a major cause of morbidity and mortality after kidney transplantation. Methods: In this transplant cohort study at the German Center of Infectious Diseases (DZIF), we evaluated all infections occurring during the first year after renal transplantation. We assessed microbial etiology, incidence rates, and temporal occurrence of these infections. Results: Of 804 renal transplant recipients (65.2% male, 51 ± 14 years), 439 (54.6%) had 972 infections within the first year after transplantation. Almost half of these infections (47.8%) occurred within the first 3 months. Bacteria were responsible for 66.4% (645/972) of all infections, followed by viral (28.9% [281/972]) and fungal (4.7% [46/972]) pathogens. The urinary tract was the most common site of infection (42.4%). Enterococcus was the most frequently isolated bacterium (20.9%), followed by E. coli (17.6%) and Klebsiella (12.5%). E. coli was the leading pathogen in recipients <50 years of age, whereas Enterococcus predominated in older recipients. Resistant bacteria were responsible for at least 1 infection in 9.5% (76/804) of all recipients. Viral infections occurred in 201 recipients (25.0%). Of these, herpes viruses predominated (140/281 [49.8%]), and cytomegalovirus had the highest incidence rate (12.3%). In the 46 fungal infections, Candida albicans (40.8%) was the most commonly isolated. Other fungal opportunistic pathogens, including Aspergillus fumigatus and Pneumocystis, were rare. Conclusions: Renal allograft recipients in Germany experience a high burden of infectious complications in the first year after transplantation. Bacteria were the predominating pathogen, followed by opportunistic infections such as cytomegalovirus. Microbial etiology varied between age groups, and resistant bacteria were identified in 10% of recipients.